Feasting on the Future: Unveiling Edible Insects as a Sustainable Food with Enriched Health Benefits - Kumar, Akash; Goyal, Nandani; Pramanik, Jhilam; Joia, Swati; Singh, Sudarshan; Prajapati, Bhupendra G. (Current Nutrition & Food Science, 2025)
Animal- and plant-based foods are considered staple foods worldwide. As the population increases, new alternative foods with higher nutritional value and sustainable nature are needed. Moreover, the current food system drastically impacts the environment and may result in unsustainability. The livestock sector significantly contributes to greenhouse gas emissions and is a major user of land and water resources. Additionally, excessive animal farming adversely affects the environment, accelerating climate change. To solve these problems, alternative and eco-friendly food resources that offer proper nutritional and health benefits are needed. Although edible insects have been used through several civilizations, they have emerged as an exciting and promising approach. Edible insects can transform various organic products into high-quality proteins with essential amino acids, including agricultural and food waste products. Edible insects are nutritionally rich and contain healthy fatty acids such as lauric acid, oleic acid, and omega 3 and 6. In addition, edible insect production requires much less resources, such as water and land, and emits significantly less greenhouse gases, thus contributing to sustainable food production. This review provides a comprehensive understanding of the nutritional profile, sustainability aspects, and health benefits of edible insects.
Keywords: crickets